Correction to: Unveiling Melanoma: A Deep Dive into Disparities at a Latin-American Cancer Institute (Annals of Surgical Oncology, (2024), 31, 9, (6097-6117), 10.1245/s10434-024-15573-6) - Ziegler-Rodriguez, Gonzalo (2024)
n the original online version of this article Luis Piedra‑Delgado's affiliation was incorrect. It is correct as reflected here. The original article was corrected.